Development of portable, application specific electronic nose for agriculture - Abu Hassan Abdullah (School of Mechatronic Engineering, University Malaysia Perlis, 2014)
The purpose of this research is to develop a portable Application Specific Electronic Nose (ASEN) to improve their capabilities. The developed instrument uses specific selected sensor arrays which were identified based on experiment and key volatile compounds of the target odorant. Humidity and temperature sensor are also being included in the instrument to measure the environmental condition.